2020
DOI: 10.3389/fphar.2020.00309
|View full text |Cite
|
Sign up to set email alerts
|

Hazards of Using Masking Protocols When Performing Ligand Binding Assays: Lessons From the Sigma-1 and Sigma-2 Receptors

Abstract: Sigma-1 and sigma-2 receptors are emerging therapeutic targets. Although the molecular identity of the sigma-2 receptor has recently been determined, receptor quantitation has used, and continues to use, the sigma-1 selective agents (+) pentazocine or dextrallorphan to mask the sigma-1 receptor in radioligand binding assays. Here, we have assessed the suitability of currently established saturation and competition binding isotherm assays that are used to quantify parameters of the sigma-2 receptor. We show tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 40 publications
(57 reference statements)
1
5
0
Order By: Relevance
“…The binding of [ 3 H] DTG to MCF7 cells showed a pK d ± SEM of [ 3 H] DTG 7.92 ± 0.04, K d = 12 nM, B max 1700 ± 400 fmol.mg −1 . We have recently shown that [ 3 H] DTG binding is reduced by (+) pentazocine with low affinity, further confirming the absence of sigma-1 receptors from MCF7 cells 20 .…”
Section: Resultssupporting
confidence: 64%
See 1 more Smart Citation
“…The binding of [ 3 H] DTG to MCF7 cells showed a pK d ± SEM of [ 3 H] DTG 7.92 ± 0.04, K d = 12 nM, B max 1700 ± 400 fmol.mg −1 . We have recently shown that [ 3 H] DTG binding is reduced by (+) pentazocine with low affinity, further confirming the absence of sigma-1 receptors from MCF7 cells 20 .…”
Section: Resultssupporting
confidence: 64%
“…Nonspecific binding was determined using 100 μM reduced haloperidol. No sigma-1 receptor "masking agent" (e.g., (+) pentazocine) was used, as this adversely affects the determination of K d and K i values at the sigma-2 receptor 20 . Assays were terminated by addition of ice-cold sigma-2 wash buffer (150 mM NaCl, 10 mM Tris-HCl; pH 7.2) and filtration, using a cell harvester, through glass fibre filters (GF/C, Sigma-Aldrich, Poole, UK).…”
Section: Methodsmentioning
confidence: 99%
“…The compiled data on cell lines reported to express σ2 receptors is shown below ( Table 4 ). These cell lines are HT29, A549/ATCC, MAD-MB-468 ( Abbas et al, 2020 ), MAD-MB-435 ( Zeng et al, 2007 ), OVCAR-3 ( Peluso et al, 2008 ), DU-145 ( Christy et al, 1999 ), and MCF7 ( Vilner et al, 1995 ). Our compounds showed varying degrees of growth inihibiton.…”
Section: Resultsmentioning
confidence: 99%
“…SA4503 has been reported to have σ1R/σ2R ratio of approximately 100‐fold, with no significant affinity to 36 other receptors, transporters or channels 35,36 . However, using masking protocols with selective ligands, the σ1R/σ2R ratio was reported to be 14‐fold in guinea pig brain membranes, although such masking protocols were shown to carry their own challenges and these data should be treated with caution 37,38 . The magnitude of the PET signal is proportional to the ratio of target density and affinity (B max /K d ).…”
Section: Discussionmentioning
confidence: 99%
“…35,36 However, using masking protocols with selective ligands, the σ1R/σ2R ratio was reported to be 14-fold in guinea pig brain membranes, although such masking protocols were shown to carry their own challenges and these data should be treated with caution. 37,38 The magnitude of the PET signal is proportional to the ratio of target density and affinity (B max /K d ). The σ2R, a transmembrane ER-resident regulator of the Niemann-Pick carrier protein, 39 contributed to the PET signals obtained in this study.…”
Section: Discussionmentioning
confidence: 99%